PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL KEDELAI VARIETAS DENA-1 DAN DEGA-1 - Charlos A. Tenmau; I G.B. Adwita Arsa; Shirly S. Oematan (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Dena-1 and Dega-1 are two soybean varieties that have been released as superior varieties, but have not been cultivated in the NTT Province. Therefore, this research aimed to evaluate the productivity of these two soybean varieties at various spacing planting in Kupang Regency. The experiment was a factorial trial laid out in a randomized block design (RBD). The first factor was soybean varieties (V), namely: Dena-1 (v1) and Dega-1 (v2) varieties. The second factor was the planting spacing (J) with five levels, namely: 40 cm x 10 cm (j1), 40 cm x 15 cm (j2), 40 cm x 20 cm (j3), 40 cm x 25 cm (j4) and 40 cm x 30 cm (j5). There were 10 combination treatments with three replications so there were 30 experimental units in total. Each experimental unit was laid in a plot of 2.0 m x 1.5 m. The data observed included: a) vegetative growth, b) generative growth, and c) supporting data. The data were analyzed using analysis of variance followed by DMRT at 5% significance level. The results showed that the interaction between treatments did not significantly affect all variables observed, however, the single factor of planting spacing and type of variety had a very significant effect on vegetative and generative growth. The 40 cm x 20 cm spacing planting gave higher seed weight per plot than the 40 cm x 25 cm and 40 cm x 30 cm spacing planting. The Dena-1 and Dega-1 varieties did not show any difference in seed weight per plot, but the weight of 100 seeds of the Dega-1 variety was greater than that of the Dena-1 variety.